Perbaikan Sistem Keselamatan dan Kesehatan Kerja di PT. X - Billy Yonathan Sutrisno; Togar W.S Panjaitan; Jani Rahardjo (Jurnal Titra, 2015)
PT. X is one of the leading furniture and also only exporting its products. One of the desire of the company is “To be one of the market leaders of furniture industry”, while the vision of PT. X is ” Producing high quality with reliable design”.This factory is currently running the system of health and safety work in the factory area. However, the improvement is still need to be done by minimizing potential risks with HIRARC(Hazard Indentification, Risk Assessment and Risk Control). The result shows 47% of activities are considered as low risk, 36% of activities are considered as moderate risk, and 17% of activities are considred as high risk. There are 4 activities categorised as high risk that must be considered which are sawdust that is inhaled by an operator, member of the body missing, member of the body and exposed side off wood that isn’t neat.